Agroindustrialização e incentivos fiscais estaduais em Goiás - PARANAIBA, Adriano de Carvalho (2012)
The aim of this study is to understand how were the territorial occupation of agribusiness in Goiás and the participation of state tax incentives in this process. Therefore, it was adopted as a hypothesis that, the dynamic agribusiness developed in a heterogeneous formation, both in the occupation of the agroindustrial complex, as in the granting of state tax incentives. To achieve the proposed objective, data from the Municipal Agricultural Research (PAM) and the Agricultural Census for 1970 until 2006, from the Brazilian Institute of Geography and Statistics (IBGE) were used to understand the phenomenon of farming dynamics in Goiás, and data from Sefaz-GO to understand state tax incentives as well. After the processing of such data in tables, maps were built in the Arcviews 10 program which had as their goal show the spatialization of the production on the territorial space of Goiás. What we realized was that, in the case of the Midwest, since the decade of 70, the state (Federal Government) has taken a strong role, creating the attractive access to this area of the agricultural frontier, fostering changes in the technological base. This action of the Federal Government created conditions incurred in the frontier region preview, on the part of the individual capitalist, as a potential area, susceptible to conversion of land use to attend not only the soybean exported sector but also to attend inputs of agribusiness demands of the South and Southeast, entering Goiás production circuit business in Brazil´s grainby favouring the penetration of the agroindustrial complex in Goiás. However, the penetration of both technological factors affecting modern agriculture as the input of the CAI occurred unevenly in Goiás, given the historical construction of Goias´ economy. To specialize the policies of tax incentives, it was realized that they spread in the municipalities of Goiás partners with the same heterogeneous structure that the modernisation of agriculture, together with the dynamics of the agricultural frontier expansion, contributing to the intensification of industrialization for the regions which were formed in this long process of historical formation of Goiás.